2018
DOI: 10.1177/1526602818820792
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Foot Vein Arterialization in No-Option Patients With Critical Limb Ischemia: A Preliminary Report

Abstract: To describe a preliminary experience in treating no-option critical limb ischemia (CLI) patients with a hybrid foot vein arterialization (HFVA) technique combining open plus endovascular approaches. Materials and Methods: Between May 2016 and January 2018, 35 consecutive patients (mean age 68±12 years; 28 men) with 36 no-option CLI limbs underwent HFVA in our center. All limbs had grade 3 WIfI (Wound, Ischemia, and foot Infection) ischemia, and the wound classification was grade 1 in 4 (11%) limbs, grade 2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…We hypothesize that a remodeling process takes place after pDVA. Ferraresi et al 8 reported the possibility of an angiographically detected remodeling process after DVA associated with clinical wound healing and high TcPO 2 measurements. We believe that longer time to wound healing in our study could be related to this remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that a remodeling process takes place after pDVA. Ferraresi et al 8 reported the possibility of an angiographically detected remodeling process after DVA associated with clinical wound healing and high TcPO 2 measurements. We believe that longer time to wound healing in our study could be related to this remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…Since incisions on the foot may have difficulties healing, some authors favour a hybrid approach performing distal anastomoses at the malleolar level, but destroying distal valves and closing side branches by endovascular means …”
Section: Venous Arterializationmentioning
confidence: 99%
“…Since incisions on the foot may have difficulties healing, some authors favour a hybrid approach performing distal anastomoses at the malleolar level, but destroying distal valves and closing side branches by endovascular means. 16,18 Limb salvage after surgical venous arterialization is variable and the prognosis is difficult to predict for the individual patient. Lu amputation and amputation could be avoided in three patients, although our later results tend to be better.…”
Section: Venous Arterializationmentioning
confidence: 99%
“…This is a relevant aspect mainly in proximal pDVA because in distal pDVA a terminal anastomosis in the distal common plantar/lateral plantar veins reduces the probability of encountering valves that might obstruct blood flow. 11 Different strategies have been suggested for valve destruction: conventional or cutting balloons, wire-/catheter-based maneuvers, 12 or an antegrade valvulotome (ie, the Limflow system). It is hypothesized that the barotrauma of a balloon may predispose to future restenosis, 13 but these changes have been seen in only cadaver angioscopic studies.…”
mentioning
confidence: 99%
“…Most authors perform venous collateral embolization on demand in case of insufficient clinical improvement, 1,5 while others recommend systematic focalization of blood flow to the wound by embolizing the proximal foot vein collaterals 14 to 28 days after the DVA procedure. 12…”
mentioning
confidence: 99%